Care of Women with Chronic Inflammatory Bowel Disease (Chronic IBD) during Pregnancy - Schmidt, Markus; Kühnert, Maritta; Kuschel, Bettina; Kehl, Sven; Schäfer-Graf, Ute Margaretha (Geburtshilfe und Frauenheilkunde, 2021)
The incidence of chronic inflammatory bowel disease (chronic IBD) in persons of reproductive age is high. Chronic IBD does not typically lead to impaired fertility. Nevertheless, the percentage of women suffering from chronic IBD who have children is lower than that of the general population, due to self-imposed childlessness. Providing women with open, unbiased information and, if necessary, helping them to overcome baseless fears should therefore be an essential part of preconception counseling. With the exception of methotrexate, most standard drugs can and should be continued during pregnancy. If the pregnancy occurs during an inactive phase of disease, the rate of complications in pregnancy should, in principle, not be higher than normal. Nevertheless, pregnant women with chronic IBD are classed as high-risk pregnancies. Organ screening in accordance with DEGUM II criteria should be carried out in every case, and women must be monitored for the potential development of placental insufficiency. Any flare-ups which occur during pregnancy should be treated in full. Vaginal delivery can be considered if there is no perianal manifestation of disease; however, the individual risk must be carefully weighed up.
CRIS-Team Scopus Importer:2021-12-24
Keywords: chronic inflammatory bowel disease; Crohn's disease; pregnancy; ulcerative colitis